The Bohr's phenomenon for analytic functions and harmonic mappings. - Mohamed Ali, Rosihan (Universiti Sains Malaysia, 2015)
In this paper, we introduce and investigate a subclass of analytic and bi-univalent functions in the open unit disk U. By using the Faber polynomial expansions, we obtain upper bounds for the coefficients of functions belonging to this analytic and bi-univalent function class. orne interesting recent developments involving other subclasses of analytic and bi-univalent functions are also briefly mentioned.